Screening for anti-influenza virus compounds from traditional Mongolian medicine by GFP-based reporter virus - Nie, Mao-Shun; Li, Xiao-He; Zhang, Sen; Zeng, Dan-Dan; Cai, Yu-Rong; Peng, Da-Xin; Jiang, Tao; Shi, Jian-Ping; Li, Jing (Frontiers in Cellular and Infection Microbiology, 2024)
Screening for effective antiviral compounds from traditional Mongolian medicine not only aids in the research of antiviral mechanisms of traditional medicines, but is also of significant importance for the development of new antiviral drugs targeting influenza A virus. The use of GFP-based reporter viruses plays a pivotal role in antiviral drugs screening by enabling rapid and precise identification of compounds that inhibit viral replication. Herein, we aimed to utilize a GFP-based reporter influenza A virus to identify potent anti-influenza compounds within traditional Mongolian medicine. Our efforts led to the discovery of three active compounds: Cardamonin, Curcumin, and Kaempferide, all of which exhibited significant antiviral properties in vitro. Subsequent analysis confirmed that their effectiveness was largely due to the stimulation of the antiviral signaling pathways of host cells, rather than direct interference with the viral components, such as the viral polymerase. This study showcased the use of GFP-based reporter viruses in high-throughput screening to unearth antiviral agents from traditional medicinal sources.